Multiple Dynamic Mechanisms of Globalization: Alternatives to Capitalism - Yu Huang (Sustainability, 2019)
As one of the most striking topics in the contemporary world economy, the discussion on globalization seems to take capitalism as the main dynamic mechanism for its practice process, i.e., capital-driven globalization. Although many researchers have proposed other alternative solutions that are crucial to the development of globalization, relevant research is still very insufficient. Based on this point, this study aims to explore the driving forces, action mechanisms, manifestations, and influences of the contemporary globalization process in a more comprehensive way, particularly focusing on the dynamic mechanisms of globalization other than capitalism, and trying to explain the interaction between various dynamic mechanisms. Overall, this paper summarizes three major (but not all) dynamic mechanisms of the contemporary globalization: capital-driven, state-driven, and inter-state cooperation-driven. These three dynamic mechanisms act on different spaces in different ways, exert different influences, and have profound interactive relations on the process of globalization. By showing a more comprehensive picture of globalization, this study attempts to explain the existing alternatives to capital-driven globalization, and encourages a more in-depth discussion of anti-globalization and regional integration as alternative options for globalization from the perspective of internal operation mechanism.